Similarity Solutions to Nonlinear Diffusion/Harry Dym Fractional Equations - Chao Yue; Guijuan Liu; Kun Li; Hanhui Dong (Advances in Mathematical Physics)
By using scalar similarity transformation, nonlinear model of time-fractional diffusion/Harry Dym equation is transformed to corresponding ordinary fractional differential equations, from which a travelling-wave similarity solution of time-fractional Harry Dym equation is presented. Furthermore, numerical solutions of time-fractional diffusion equation are discussed. Again, through another similarity transformation, nonlinear model of space-fractional diffusion/Harry Dym equation is turned into corresponding ordinary differential equations, whose two similarity solutions are also worked out.